Development of Chemical Bonding LKPD Assisted by Augmented Reality with a Deep Learning Approach and its Effect on Learning Activities and Higher Level Thinking Skills (Hots) of Eleventh Grade High School Students - Dita Novita Rini; Eli Rohaeti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to develop a Student Worksheet (LKPD) on Chemical Bonding assisted by Augmented Reality (AR) based on deep learning and to examine its feasibility, practicality, and effectiveness in improving learning activities and higher-order thinking skills (HOTS) of high school students. The research employed a 4D development model (define, design, develop, and disseminate) using a pretest posttest control group design involving 11th grade students. Research instruments included expert validation sheets, learning activity questionnaires, and HOTS test instruments. Data were analyzed using descriptive and inferential statistical methods. The results indicated that the AR-based LKPD met very feasible and practical criteria based on expert judgment and student responses. Furthermore, there was a statistically significant difference between the experimental and control groups in learning activities and HOTS achievement (p = 0.005). The increase in HOTS scores in the experimental group was categorized as moderate, indicating meaningful learning gains. These findings demonstrate that the AR-assisted Chemical Bonding LKPD is effective as an innovative learning medium for supporting students’ understanding of abstract chemistry concepts and fostering higher-order thinking skills.